CASHFLOW AND DISCOUNTRATE FOR THE EVALUATION OF INVESTMENT PROJECTS - Mavila Hinojoza, Daniel (2005)
Projects are assessed through different methods. The VNA and the TIR are the most used, being the crucial factors the cash flow and the discount rate. This article is aimed at making it clear what discount rate should be appropriate, taking into account the fund contributor criterion. We think that this subject has not been treated in depth by the respective theory.